Herlyn-Werner-Wunderlich Syndrome: Challenges in Early Diagnosis - Natasha, Ayu; Punarbawa, Gede; Noviyanti (Ridwan Institute, 2025)
Herlyn-Werner-Wunderlich syndrome (HWWS) is a rare Müllerian duct anomaly characterized by the triad of uterine didelphys, blocked hemivagina, and ipsilateral renal agenesis. The syndrome often remains asymptomatic until after menarche, when symptoms related to haematocolpos, such as severe dysmenorrhea, become apparent. This study presents a case of a 14-year-old female who presented to the Urogynecology Department with complaints of severe dysmenorrhea. Diagnosis was confirmed through CT scan and ultrasound imaging, which revealed the typical triad of HWWS. The treatment involved the surgical incision of the vaginal septum to address the obstructed hemivagina. While HWWS is usually diagnosed after the onset of menstruation due to the development of haematocolpos, early detection during infancy could help prevent acute complications. The study emphasizes that gynecologists should consider HWWS in the differential diagnosis when patients present with cyclic pelvic pain, monthly alterations in menstrual flow, pelvic masses, or renal agenesis. Early identification and management of HWWS are crucial to prevent long-term complications.